Physiological Traits Affecting the Distribution and Wintering Strategy of the Bat Tadarida teniotis - Arlettaz, Raphael; Ruchet, Catherine; Aeschimann, John; Brun, Edmond; Genoud, Michel; Vogel, Peter (Zenodo, 2000)
(Uploaded by Plazi for the Bat Literature Project) The ability to enter torpor at low ambient temperature, which enables insectivorous bats to survive seasonal food shortage, is often seen as a prerequisite for colonizing cold environments. Free-tailed bats (Molossidae) show a distribution with a maximum latitudinal extension that appears to be intermediate between truly tropical and temperate-zone bat families. We therefore tested the hypothesis that Tadarida teniotis, the molossid species reaching the highest latitude worldwide (46? N), lacks the extreme physiological adaptations to cold that enable other sympatric bats to enter further into the temperate zone. We studied the metabolism of individuals subjected to various ambient temperatures in the laboratory by respirometry, and we monitored the body temperature of free-ranging individuals in winter and early spring in the Swiss Alps using temperaturesensitive radio-tags. For comparison, metabolic data were obtained from Nyctalus noctula, a typically hibernating vespertilionid bat of similar body size and convergent foraging tactics. The metabolic data support the hypothesis that T. teniotis cannot experience such low ambient temperatures as sympatric temperate-zone vespertilionid bats without incurring much higher energetic costs for thermogenesis. The minimum rate of metabolism in torpor was obtained at 7.5?-10?C in T. teniotis, as compared to 2.5?-5?C in N. noctula. Field data showed that T. teniotis behaves as a classic thermo-conforming hibernator in the Alps, with torpor bouts lasting up to 8 d. This contradicts the widely accepted opinion that Molossidae are nonhibernating bats. However, average body temperature (10?-13?C) and mean arousal frequency (3.4 d in one bat in January) appear to be markedly higher than in other temperatezone bat species. At the northern border of its range, T. teniotis selects relatively warm roosts (crevices in tall, south-exposed limestone cliffs) in winter, where temperatures oscillate around 10?C. By this means, T. ...